Intergenerational income mobility in Sweden: A look at the spatial disparities across municipalities. Issue 4 (10th August 2021) - Michelangeli, Alessandra; Östh, John; Türk, Umut
Abstract: This paper provides a comprehensive overview of intergenerational income mobility in Sweden. Intergenerational income mobility is considered in both relative and absolute terms, and the analysis is carried out at the individual and municipality level. We use multilevel models to explore the correlation between upward mobility and social, economic and demographic characteristics of cities. We account for a wider set of local characteristics, such as the spatial distribution of income inequality within city and housing affordability that have not been considered by previous studies analysing social mobility in the United States or other European countries. The analyses are carried out on three subpopulations: offspring who live in a different municipality than their parents (spatial mobile population); offspring who live in the municipality where they grew up (spatial immobile population); offspring belonging to visible minority groups. Our results show substantial differences across municipalities, meaning that the particular combination of municipality attributes contributes to shaping the chance of status attainment among young generations. Highly mobile municipalities have more significant human capital, more residential segregation by income, more local levels of income inequality, and greater accessibility to jobs. The results indicate that dependence on parents' support and network for upward mobility is of less importance, and that spatial mobility (regardless of background) especially to larger urban areas is associated with upward mobility for the children. Abstract: Este artículo ofrece una sinopsis general de la movilidad intergeneracional de la renta en Suecia. La movilidad intergeneracional de la renta se considera tanto en términos relativos como absolutos, y el análisis se realiza a nivel individual y municipal. Se usan modelos multinivel para estudiar la correlación entre la movilidad ascendente y las características sociales, económicas y demográficas de las ciudades. Se tuvo en cuenta un conjunto amplio de características locales, como la distribución espacial de la desigualdad de la renta dentro de la ciudad y la asequibilidad de la vivienda, que no han sido consideradas por estudios anteriores de análisis de la movilidad social en Estados Unidos u otros países europeos. Los análisis se realizan sobre tres subpoblaciones: los hijos que viven en un municipio diferente al de sus padres (población espacial móvil); los hijos que viven en el municipio donde crecieron (población espacial inmóvil); y los hijos pertenecientes a grupos minoritarios visibles. Los resultados muestran diferencias sustanciales entre municipios, lo que significa que la combinación particular de atributos del municipio contribuye a configurar la posibilidad de alcanzar un estatus entre las generaciones jóvenes. Los municipios con alta movilidad tienen un capital humano más importante, más segregación residencial por ingresos, más niveles locales de desigualdad de ingresos y mayor accesibilidad al empleo. Los resultados indican que la dependencia del apoyo y la red de contactos de los padres para la movilidad ascendente es menos importante, y que la movilidad espacial (independientemente del origen), especialmente hacia zonas urbanas más grandes, está asociada a la movilidad ascendente de los hijos. Abstract: 本稿は、スウェーデンにおける世代間所得移転を包括的に概観する。世代間所得移転を相対的および絶対的に検討し、個人レベルおよび自治体レベルで分析を行った。都市の上方移動性と社会的、経済的、人口統計学的特性との相関性を、マルチレベルモデルを用いて検討した。本稿では、米国やその他の欧州諸国における社会移動を分析した既存研究では考慮されていなかった、都市内の所得不平等の空間的分布や住宅取得能力など、より広範な地域特性を考慮に入れている。 分析は3つのサブグループについて行われた。1)両親とは異なる自治体に住んでいる人(空間移動集団)。2)自分が育った自治体に住んでいる人(空間的に動かない集団)。3)ヴィジブル・マイノリティのグループに属する人。 結果から、自治体によってかなりの差異が示されるが、これは、自治体属性の特定の組合せが若い世代の地位達成の機会形成に寄与することを意味する。社会移動能力の高い自治体ほど、人的資本が充実しており、所得による居住地の分離が進んでおり、地域レベルでの所得不平等の差が大きく、仕事を得やすい状況である。結果から、上向きの移動性に対する親の支援とネットワークへの依存は重要ではなく、特により大きな都市部への空間的移動性が子供の上向きの移動性に関連していることが示された。